Relationship Between Stress Levels and Eating Disorders Among Adolescents A Cross-Sectional Study - Diah Agustin, Eva; Anggari, Roshinta Sony; Maulida Nurfazriah (poltekkes kemenkes mataram, 2025)
Stress is defined as a state of mental and emotional turmoil. Stress can lead to abnormal eating behaviors and eating disorders. An eating disorder is defined as an eating disorder caused by a person's anxiety. Reactions to stress can cause increased appetite or vice versa. The purpose of this study was to identify the relationship between stress levels and eating disorders in adolescents. The research method used was a cross-sectional study with a sample size of 224 respondents. The sample method used was random sampling, which was carried out in July 2023. Data were collected through the DASS-42 questionnaire and the EAT-26 questionnaire. The results of the Spearman's Rank correlation analysis show that p = 0.000 or smaller than Î± = 0.005, so it can be concluded that there is a relationship between stress levels and eating disorders in adolescents. Teenagers are expected to know how to manage stress and can consult with parents, teachers, or peers. Take time for a vacation to tourist attractions/entertainment, this is expected so that adolescents are not too stressed with practice preparation, many tasks, and personal problems.